2005
DOI: 10.1189/jlb.0904532
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-mediated regulation of activating and inhibitory Fcγ receptors in human monocytes

Abstract: Fc gamma receptors (Fc gammaR) trigger inflammatory reactions in response to immunoglobulin-opsonized pathogens and antigen-antibody complexes. The coordinate expression of activating and inhibitory Fc gammaR ensures the homeostasis of immune complex-driven inflammatory responses. In this study, we used antibodies with preferential binding for activating Fc gammaRIIa and inhibitory Fc gammaRIIb receptors to investigate the expression and regulation of Fc gammaRII isoforms in human monocytes. Cross-linking of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 53 publications
(47 reference statements)
5
39
0
Order By: Relevance
“…Other studies have shown increased expression of activating Fc␥R on monocyte/macrophages in patients with active RA associated with enhanced monocyte effector functions in vitro (12,13), whereas increased expression of inhibitory Fc␥RIIb has been shown to prevent monocyte activation in RA (14). Studies of mouse models of RA support these findings in that strains susceptible to collagen-induced arthritis show skewed Fc␥R expression toward activating isoforms (15).…”
Section: Discussionsupporting
confidence: 71%
“…Other studies have shown increased expression of activating Fc␥R on monocyte/macrophages in patients with active RA associated with enhanced monocyte effector functions in vitro (12,13), whereas increased expression of inhibitory Fc␥RIIb has been shown to prevent monocyte activation in RA (14). Studies of mouse models of RA support these findings in that strains susceptible to collagen-induced arthritis show skewed Fc␥R expression toward activating isoforms (15).…”
Section: Discussionsupporting
confidence: 71%
“…Data from our group demonstrated differential modulation of Fc␥RIIb expression in human monocytes and neutrophils by cytokines suggesting that alterations in cytokine levels common during inflammatory and autoimmune reactions could cause changes in Fc␥RIIb expression (21)(22)(23). A role for hormones in the reg- ulation of FCGR2B gene expression was revealed when dihydrotestosterone was found to inhibit Fc␥RIIb expression, suggesting a role for sex hormones in the onset and progression of autoimmune diseases (24).…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, mAb 7.3 exhibits preferential binding to Fc␥RIIb, while maintaining interaction with Fc␥RIIa (gray histograms, Fig. 1A, inset) (18). Staining with IV.3-FITC resulted in similar MFIs on iDC (51.8 Ϯ 2.9) and mDC (56.7 Ϯ 3.9) suggesting that, Fc␥RIIa expression is sustained at comparable levels at early and advanced stages of DC maturation (Fig.…”
Section: Dynamic Variations In Fc␥r Expression Occur During DC Maturamentioning
confidence: 96%
“…Lysates obtained from Ma, iDCs, and mDCs were immunoprecipitated with pan-Fc␥RII mAb clone FLI8.26 that binds both Fc␥RIIa and Fc␥RIIb (12,19). The immunoprecipitated proteins were run on SDS-PAGE followed by immunoblotting with specific Abs raised against the intracellular domain of Fc␥RIIa (260) and Fc␥RIIb (Fc␥RIIB/IC), respectively (18). Lysates obtained from A375 melanoma cells transfected with rFc␥RIIA (IIA), Fc␥RIIB2 (IIB2), or vector only (NT) indicate the specificity of the immunoblotting Abs (Fig.…”
Section: Dynamic Variations In Fc␥r Expression Occur During DC Maturamentioning
confidence: 99%
See 1 more Smart Citation